AN EVALUATION OF TWO ENGLISH TEXTBOOKS USED BY FOURTH-GRADE STUDENTS IN TWO ELEMENTARY SCHOOLS IN BANDUNG, WEST JAVA - Suharja, Anggi Auliyani (2017)
Penelitian ini bertujuan untuk mengetahui apakah dua buku teks bahasa Inggris yang digunakan oleh dua sekolah dasar di Bandung memenuhi kriteria sebagai buku teks yang sesuai untuk anak-anak. Penelitian ini menggunakan metode deskriptif kualitatif. Subjek penelitian ini merupakan dua buku teks yaitu "Grow with English" dan "English Chest.". Data penelitian ini dikumpulkan melalui analisis dokumen dalam bentuk evaluasi buku teks menggunakan sebuah rubrik yang mencakup kriteria buku teks yang sesuai untuk anak-anak yang diadaptasi dari beberapa ahli. Selain itu, wawancara bersama guru dan murid juga dilakukan untuk data dari hasil evaluasi buku teks. Dari hasil penelitian ini, telah ditemukan bahwa buku yang diteliti telah memenuhi kriteria buku yang sesuai untuk anak-anak. Kelebihan kedua buku teks ini terindikasi dari aspek tampilan, isi, dan bahasa. Hasil wawancara juga menunjukkan bahwa kedua buku teks ini menarik dan mudah dipelajari.,---This study aimed at investigating whether two English textbooks used by two elementary schools in Bandung fulfill the criteria of a good textbook for young learners. Descriptive qualitative method was employed as the design of the research. The subjects of this research were two textbooks namely Textbook 1 (T1) entitled "Grow with English" and Textbook 2 (T2) entitled "English Chest.". The data were collected from document analysis in the form of textbook evaluation using a rubric related to criteria of good textbooks proposed by some experts. Besides, interview with the students and the teachers were also conducted to support the data from the result of textbooks evaluation. It was found that the two textbooks likely met the criteria of a good English textbook for young learners. Those strengths were indicated from its presentation, content, and language. That statement was also supported by the interview with the students who claimed that the textbooks are interesting and easy to follow. Meanwhile, in the interview the teachers commented that the textbooks are helpful and accommodating for teaching.